2019
DOI: 10.1038/s41398-019-0635-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel genome-wide associations for anhedonia, genetic correlation with psychiatric disorders, and polygenic association with brain structure

Abstract: Anhedonia is a core symptom of several psychiatric disorders but its biological underpinnings are poorly understood. We performed a genome-wide association study of state anhedonia in 375,275 UK Biobank participants and assessed for genetic correlation between anhedonia and neuropsychiatric conditions (major depressive disorder, schizophrenia, bipolar disorder, obsessive compulsive disorder and Parkinson's Disease). We then used a polygenic risk score approach to test for association between genetic loading fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 84 publications
4
49
0
Order By: Relevance
“…PRSs were included in the analysis if: (1) there was evidence of significant genetic correlation of the trait with BD and (2) we had at least 80% power to detect PRS association in a general case-only analysis of our data assuming 50% prevalence of the sub-phenotype. We began by considering PRSs for major psychiatric disorders (BD 33 , SCZ 34 , MDD 35 , ADHD 36 , anxiety 37 , PTSD 19 , OCD 38 , anorexia nervosa 39 , alcohol use disorder 40 , and insomnia 41 ) and personality and lifestyle traits related to BD (alcohol consumption 40 , educational attainment (EA) 42 , risk-taking 43 , subjective well-being 44 , neuroticism 45 , anhedonia 46 , and body mass index (BMI) 47 ). The GWAS summary statistics were restricted to well-imputed variants (INFO > 0.9) when information on imputation quality was available.…”
Section: Methodsmentioning
confidence: 99%
“…PRSs were included in the analysis if: (1) there was evidence of significant genetic correlation of the trait with BD and (2) we had at least 80% power to detect PRS association in a general case-only analysis of our data assuming 50% prevalence of the sub-phenotype. We began by considering PRSs for major psychiatric disorders (BD 33 , SCZ 34 , MDD 35 , ADHD 36 , anxiety 37 , PTSD 19 , OCD 38 , anorexia nervosa 39 , alcohol use disorder 40 , and insomnia 41 ) and personality and lifestyle traits related to BD (alcohol consumption 40 , educational attainment (EA) 42 , risk-taking 43 , subjective well-being 44 , neuroticism 45 , anhedonia 46 , and body mass index (BMI) 47 ). The GWAS summary statistics were restricted to well-imputed variants (INFO > 0.9) when information on imputation quality was available.…”
Section: Methodsmentioning
confidence: 99%
“…Schizophrenia polygenic risk score was found to predict negative symptoms both in patients and in the general population 140‐143 . Also, anhedonia and low sociability demonstrated moderate genetic correlations with schizophrenia 144,145 .…”
Section: Validity Evidencementioning
confidence: 97%
“…The authors also reported high genetic correlations between anhedonia and depression, as well as a moderate genetic correlation with schizophrenia [73]. Moreover, a higher anhedonia polygenic score predicted reduced brain volumes, including in the NAcc and mPFC, as well as altered white matter integrity in multiple pathways [73].…”
Section: Depressionmentioning
confidence: 98%
“…Strikingly, a UK Biobank meta-GWAS (n = 375,275) identified an association between anhedonia and a locus in DCC, which was the most statistically significant finding [73]. The authors also reported high genetic correlations between anhedonia and depression, as well as a moderate genetic correlation with schizophrenia [73].…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation